Checking for Understanding Digitally During Content Area Learning. (21st July 2015) - Fisher, Douglas; Frey, Nancy
Abstract : In this column, we focus on the various ways that teaches can check for understanding. We organize the information into four categories: speaking and listening, audience response, writing, and projects. For each of these areas, we provide digital tools that teachers can use to determine students' understanding of the text.